Forest fuel beds and carbon in Mexico - Flores-Garnica, J. Germán; Wong-González, Julio C.; Paz-Pellat, Fernando (Instituto de Ecología, A.C., 2018)
Forest fuels play an important role in the field of global warming, therefore a proper estimation will allow a decrease of the uncertainty levels of carbon (C) contents. This paper describes the evaluation process for loads of duff (litter and fermentation layer, M) and downed woody material (MLC). A summary of the C content reported in Mexico is also presented. The evaluation of these fuels has been primarily based on the strategy of planar intersections. The contents of C were determined using different percentages of C content with respect to mass (dry weight), ranging from 47.5% to 66.9%, although a percentage of 50% was used, in general. Most works has been focused on temperate ecosystems, where 9.43 Mg C ha-1 of MLC was reported. While for tropical forests there was 8 Mg C ha-1. For M was reported 6.91 Mg C ha-1 and 4.25 Mg C ha-1 in duff, and 5.88 Mg C ha-1 and 1.39 Mg C ha-1 in the fermentation layer for temperate regions and tropical forests, respectively. It is concluded that there is little information on C evaluations regarding M and MLC. In addition, other regions should be considered and standardized evaluation procedures should be used. In this way, the information generated will be comparable and compatible. This will not only reduce levels of uncertainty, but also present information at different scales.